Perpindahan muara Sungai Bogowonto di daerah Pantai Congot Kabupaten Kulonprogo - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
Bogowonto river mouth is one of the river mouths which flows to the Indian Ocean in the Kulonprogo beach area, located exactly in Congot beach. This river mouth has been shifting to the west direction cause the change of morphology of river body in the beach area and its surroundings. The shift of Bogowonto river mouth is caused by both interactions of terrestrial exogenic process such as river flows and oceanic processes such as wind, waves, and tide, which generate long shore currents. In the Congot beach area, this interaction has produced domination offorce moving to the west direction and therefore generating migration of sediment to the same direction along the beach. The migration of sediment closes the mouth river from eastern riverbank In the western side, the river bank is eroded continually due to the exogenic processes therefore the river mouth will move to the west direction in the long term. The interaction of exogenic processes depends on the seasons. In the dry season where the river debit is low, the wind and wave come from the southeast direction will generate longshore currents moving to the west direction. This condition will produce sedimentation process to the same direction therefore the river mouth will be closed. In the wet season where river debit is high, the wind and wave mostly come from the southwest direction will generate longshore currents moving to the east direction. At this time, the river mouth is opened. The opening of river mouth happens in the west side of river mouth therefore in the long term the river mouth will continue to move to the west. The moving of Bogowonto river mouth to the west direction has created a new stream near the beach line called Pasir River. This river flows to the west direction parallel to the beach line. The same pattern is showed by Lereng River, which is located more to the upper stream, but unlike Pasir River, this river flows to the east direction headed to Bogowonto River. The formation of Lereng River is similar with the formation of Pasir River when the beach line was still near Lereng River. Based on this condition, we conclude that Congot beach has been prograded. During the progradation there have been several shift of the river mouth.